2014
DOI: 10.1175/jcli-d-13-00336.1
|View full text |Cite
|
Sign up to set email alerts
|

Using an AGCM to Diagnose Historical Effective Radiative Forcing and Mechanisms of Recent Decadal Climate Change

Abstract: An atmospheric general circulation model is forced with observed monthly sea surface temperature and sea ice boundary conditions, as well as forcing agents that vary in time, for the period 1979-2008. The simulations are then repeated with various forcing agents, individually and in combination, fixed at preindustrial levels. The simple experimental design allows the diagnosis of the model's global and regional time-varying effective radiative forcing from 1979 to 2008 relative to preindustrial levels. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 77 publications
1
60
0
Order By: Relevance
“…Contribution of the direct land response to anthropogenically induced external forcing (CO 2 , aerosols, and land-use change) on the recent increase in SAT and frequency of hot summers over the NH land areas was found to be robust [22,72]. These findings [14,22,[71][72][73][74][75] explained new aspects of the direct climate response to the external forcing including the rapid tropospheric adjustment.…”
Section: Role Of Land Surface Responsementioning
confidence: 83%
See 2 more Smart Citations
“…Contribution of the direct land response to anthropogenically induced external forcing (CO 2 , aerosols, and land-use change) on the recent increase in SAT and frequency of hot summers over the NH land areas was found to be robust [22,72]. These findings [14,22,[71][72][73][74][75] explained new aspects of the direct climate response to the external forcing including the rapid tropospheric adjustment.…”
Section: Role Of Land Surface Responsementioning
confidence: 83%
“…Here, the direct response to the CO 2 forcing over the land (Fig. 4a, b) is essential for the land surface warming particularly over the Northern Hemisphere (NH) extratropics [22,71,72]. As a result, projected future changes in the landsea thermal contrast and associated atmospheric circulation over the NH extratropics [73][74][75] are clearly affected by the direct land response to the CO 2 forcing [71].…”
Section: Role Of Land Surface Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the different time at which these models were actively used, the SST and sea ice fields differed slightly among models. The amip-piForcing experiment develops some of the ideas from Andrews (2014) and is one of the CFMIP3 experiments; for additional details and examples see Webb et al (2017), GA16, and Z16. For each of the three AGCMs, five ensemble members have been used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous attribution studies suggest that the changes in SSTs, GHG concentrations, and AA precursor emissions through aerosol-radiation and aerosol-cloud interactions are all important factors for the SFND pattern and associated drought over North and northeastern China (e.g., Kwon et al, 2007;Feng and Hu, 2008;Kosaka and Xie, 2013;Andrews, 2014;Gao et al, 2014aGao et al, , 2014bKamae et al, 2014aKamae et al, , 2014bQian et al, 2014;Song et al, 2014;Trenberth et al, 2014;Urabe and Maeda, 2014;Folini and Wild, 2015;Ueda et al, 2015;Wilcox et al, 2015;Zhang and Zhou, 2015). Previous studies have also revealed that decadal climate variability over East Asia is associated with low-frequency SST variability over the Pacific Ocean (e.g., Kwon et al, 2007, Kosaka andXie, 2013;Kamae et al, 2014a;Trenberth et al, 2014;Ueda et al, 2015) and Atlantic Ocean (Feng and Hu, 2008;Kamae et al, 2014a;Qian et al, 2014) via atmospheric teleconnections.…”
Section: Introductionmentioning
confidence: 99%